Information Access for Community Through Electronic Media for Improving the Knowledge of Fish Cultivation in Rebaq Rinding Village, Muara Muntai Sub-District, Kutai Kartanegara, East Kalimantan - Eko Sugiharto; Eko Sugiharto (AIBPM Publisher, 2021)
Accessing information through electronic media is unfamiliar thing for the community since it is essential in improving their insight in order to support the increase of their fish production. This research was performed in Rebaq Rinding Village, Muara Muntai Sub-District Kutai Kartanegara District. Census method was used in this research, employing 30 fish cultivators in Rebaq Rinding Village. The objective of this research is to find out the type of information media used by fish cultivator community. This research found that the electronic information accessed by the community of fish cultivator in Rebaq Rinding Village is in the form of mobile phone and television. Among the information they access includes entertainment, watching youtube, searching for recent information and watching television. In terms of information concerning fishery, they access information of how to spawn fish correctly and how to make natural feed for the fish.